1972
DOI: 10.1159/000208458
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Activities and Glutathione Content of Erythrocytes in the Newborn: Comparison with Red Cells of Older Normal Subjects and those with Comparable Reticulocytosis

Abstract: 20 enzymatic activities and the glutathione content of newborn erythrocytes are compared (a) to normal and (b) to comparably reticulocyte-rich nonneonatal red cells. Six were very high in comparison to either control group (GSH, PGK, Enol., G-3-PD, GPI, G-6-PD). Five were very low (ACHE, RPK, GSH-Px, AK and PFK). The mean of the remainder differed from the mean of comparably reticulocyte-rich blood by less than 1 SD of the latter mean. Cord erythrocytes exhibit a characteristic metabolic pattern not explained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
2

Year Published

1974
1974
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 18 publications
4
31
2
Order By: Relevance
“…Low activities of glutathione peroxidase in cord blood were previously reported by many authors (22)(23)(24)(25)(26)(27)(28) It is worth mentioning that no correlation was found between the levels of erythrocyte antioxidant enzymatic activities present in cord blood and the levels of bilirubin during the first days of life.…”
Section: Discussionmentioning
confidence: 81%
“…Low activities of glutathione peroxidase in cord blood were previously reported by many authors (22)(23)(24)(25)(26)(27)(28) It is worth mentioning that no correlation was found between the levels of erythrocyte antioxidant enzymatic activities present in cord blood and the levels of bilirubin during the first days of life.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, enzyme activities in neonatal erythrocytes have to be compared with cell populations of similar age distribution. Most authors compared neonatal erythrocytes with blood of comparable reticulocytosis (Konrad et al (13), Gahr et al (6), Oski (16)). The number of reticulocytes, however, is a very uncertain marker for the mean cell age of the whole cell population, for reticulocytes lose their substantia granulofilamentosa after 2 days; later on the young cells cannot be distinguished from old cells by visual methods.…”
Section: Discussionmentioning
confidence: 99%
“…Four other enzymes were found to have significantly higlier activities in the neonate than in adults with reticulocytosis. Four enzymes, including adenylate kinase, were found to have lower activities in the neonate than in adults with or without reticulocytosis [12]. Thus, tliere are many differences in enzyme activity between erythrocytes from neonates and from adults, some of which appear to be related to the age of the cell.…”
Section: Aprt In Young and Old Cellsmentioning
confidence: 95%
“…T h e activities of a number of enzymes have been found to be higlier in erythrocytes from neonates than from adults [12]. However, these changes do not all correlate well with tlie age of the erythrocyte.…”
Section: Aprt In Young and Old Cellsmentioning
confidence: 96%